2016
DOI: 10.1002/mabi.201600250
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Polycaprolactone Carbon Nanotube Composite Scaffolds for Cardiac Tissue Engineering

Abstract: Fabrication of tissue engineering scaffolds with the use of novel 3D printing has gained lot of attention, however systematic investigation of biomaterials for 3D printing have not been widely explored. In this report, well-defined structures of polycaprolactone (PCL) and PCL- carbon nanotube (PCL-CNT) composite scaffolds have been designed and fabricated using a 3D printer. Conditions for 3D printing has been optimized while the effects of varying CNT percentages with PCL matrix on the thermal, mechanical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 56 publications
2
85
1
Order By: Relevance
“…In this study, 3D-printed PCL scaffolds were used because the use of 3D printing technology allows for custom-designed scaffolds with controlled microstructures and interconnected porous structures [ 44 , 45 ]. With the rapid development of tissue engineering, 3D-printed scaffolds have seen widespread use in bone tissue engineering [ 46 ], cartilage tissue engineering [ 3 ], cardiac tissue engineering [ 47 ], and so on. In addition, PCL is one of the most commonly used thermoplastic polymers for 3D printing due to its prior FDA approval, biocompatibility, and biodegradability [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 3D-printed PCL scaffolds were used because the use of 3D printing technology allows for custom-designed scaffolds with controlled microstructures and interconnected porous structures [ 44 , 45 ]. With the rapid development of tissue engineering, 3D-printed scaffolds have seen widespread use in bone tissue engineering [ 46 ], cartilage tissue engineering [ 3 ], cardiac tissue engineering [ 47 ], and so on. In addition, PCL is one of the most commonly used thermoplastic polymers for 3D printing due to its prior FDA approval, biocompatibility, and biodegradability [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among various self‐healing techniques, reversible bonds are more attractive . Polycaprolactone (PCL), as a kind of U.S. Food and Drug Administration FDA‐approved biodegradable polymer, has been widely applied in tissue engineering, such as artificial skin . Self‐repairing is crucial in the applications of the recovery of materials from inchoate damages .…”
Section: Methodsmentioning
confidence: 99%
“…From these pictures, it is concluded that the printability and scaffolds characteristics were not affected by the presence of the nanofiller. In the polymer composite, the formation of chemical bonds between the TrGO and the PCL was not observed, and the overlapping and diminishing bands of the PCL could indicate that there was either electrostatic interactions or physical adsorption between the polymer and conductive particles [60]. Figure 4a shows representative photographs of the scaffolds as recorded by the 3D printer camera after finishing each layer.…”
Section: Characterization Of the Composite Materialsmentioning
confidence: 99%